Fracture Susceptibility in Non-Vital Apex Teeth Following Various Modified Apexification Procedure – An In Vitro Study - NJ Nagaraj; Peyush Pratap Singh Sikarwar; Debkant Jena; Rini Gangwal; Ipsita Mohanty; Adnan Haider Rizvi (Journal of Pharmacy and Bioallied Sciences)
Introduction and Objective: The purpose of this research was to evaluate and compare the fracture resistance of juvenile teeth that were simulated and strengthened with two different root canal backfilling combinations (gutta-percha/AH26) and biodentine (BD) as apical barriers. Materials: Five groups (n = 10) of removed human maxillary incisors were randomly assigned. There was no instrumentation of the positive control group. To replicate juvenile teeth, coronal access was established for the other groups, and root canals were instrumented using the ProTaper up to F5. Six Peeso reamers were then permitted to pass 1 mm beyond the apex to size 6 (1.7 mm). Either mineral trioxide aggregate (MTA) or BD apical barrier was used to fill the top 4 mm of their root canals, and either gutta-percha or AH26 obturation combination was used as the backfill. Coronal access cavities were restored using composite resin. Universal testing equipment was used to record the maximum load required for each tooth to fracture. Analysis of variance was used to examine the data. Results: Compared to the negative control groups, the non-instrumented Group I had the greatest fracture resistance and varied considerably (P < 0.05). In contrast, regardless of the backfilling combination, there was no discernible difference between the BD and MTA groups (P > 0.05). Conclusion: In terms of resistance to root fracture, there was no difference between the backfilling combination and the MTA and BD apical barriers.